2021
DOI: 10.2217/fon-2021-0197
|View full text |Cite
|
Sign up to set email alerts
|

The Significant Role of a Functional Polymorphism in the NF-κB1 Gene in Breast Cancer: Evidence from an Iranian Cohort

Abstract: Aims: Breast cancer (BC) is one of the most common cancers among women. The influence of genetic variations on BC risk has been thus far assessed via genome-wide association studies. NF-κB has been recognized as a major player in BC progression. In this study, the association between rs28362491 and BC was evaluated in a population from northeastern Iran. Materials & methods: This study was conducted on 476 patients with BC and 524 healthy controls. The genotyping method used was an amplification-refractory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…This p65/p50 heterodimer plays a key role in NF-κB function [ 33 , 34 , 35 ]. In several cancer types, including CRC, lung cancer, blood cancer, and pancreatic cancer, etc., researchers have observed constitutive activation of this particular family [ 36 , 37 , 38 , 39 ].…”
Section: Genetic Changes Of Nf-κb Signaling In Crcmentioning
confidence: 99%
See 2 more Smart Citations
“…This p65/p50 heterodimer plays a key role in NF-κB function [ 33 , 34 , 35 ]. In several cancer types, including CRC, lung cancer, blood cancer, and pancreatic cancer, etc., researchers have observed constitutive activation of this particular family [ 36 , 37 , 38 , 39 ].…”
Section: Genetic Changes Of Nf-κb Signaling In Crcmentioning
confidence: 99%
“…Importantly, a recent study has detected a genetic variation within the promoter segment of the NF-κB1 gene. This genetic variation entails a 4-base pair (bp) insertion/deletion (94ins/delATTG) positioned between two presumed critical regulatory components in the promoter, specifically AP-1 and κB [ 36 ]. Interestingly, the research found that people who have two copies of this deletion (94del/delATTG) are more likely to develop ulcerative colitis, a chronic inflammatory bowel disease predominantly affecting the colon.…”
Section: Genetic Changes Of Nf-κb Signaling In Crcmentioning
confidence: 99%
See 1 more Smart Citation